THE INFLUENCE OF WORD OF MOUTH COMMUNICATION TOWARDS BRAND IMAGE OF IPHONE ON STUDENT OF POLITICAL SCIENCE AND SOCIAL SCIENCE FACULTY UNIVERSITY OF RIAU - Lidya Febriana; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research starts on the behavioristik learning theory, This theory assumes that human behavior is a process of learning. This means, if a response given by a person to a stimulus is true and he knew it, then our satisfaction will be achieved and the Association strengthened. In this research word of mouth communication looking at how a recipient of word of mouth communication of influence can lead to brand image iphone, word of mouth communication that occurs naturally and simple unwittingly introduced the iphone. The purpose of this research is to determine, whether there is an influence of word of mouth communication towards brand image of iphone on student of Political Science and Social Science Faculty University of Riau.The method used in this study is a quantitative method of explanation. Data collection techniques in this study using a questionnaire. The number of samples for this study were 166 respondents. Sampling using Accidental sampling and using propotional sampling techniques. To determine how much influence these two variables, the researchers used a simple linear regression analysis. Questionnaire for data processing, carried out using the program Statistics Product And Service Solutions (SPSS) version of Windows 23.Results of research on the influence of word of mouth communication towards brand image of Iphone on student of political science and social science faculty university of Riau regression coefficient values obtained in this study is Y = 4,682 + 0,523 X with significance level 0,006 that smaller than α = 0.05. This means that there is the influence of word of mouth communication towards brand image of iphone on student of political science and social science faculty university of Riau of 52,6% and in the category of influential medium. The percentages indicate that the word of mouth communication towards brand image of iphone wit H0 is rejected and Ha accepted.